2001
DOI: 10.1002/1097-0290(20010105)72:1<41::aid-bit6>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Succinic acid production with reduced by‐product formation in the fermentation of Anaerobiospirillum succiniciproducens using glycerol as a carbon source

Abstract: Succinic acid was produced by fermentation of Anaerobiospirillum succiniciproducens using glycerol as a carbon source. When cells were anaerobically cultured in a medium containing 6.5 g/L glycerol, a high succinic acid yield (133%) was obtained while avoiding the formation of by-product acetic acid. The gram ratio of succinic acid to acetic acid was 25.8:1, which is 6.5 times higher than that obtained using glucose (ca. 4:1) as a carbon source. Therefore, succinic acid can be produced with much less by-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 0 publications
1
93
2
2
Order By: Relevance
“…In a study with Anaerobiospirillum succiniproducens, succinic acid production from glycerol or glucose fermentations with a carbon dioxide atmosphere, revealed that glycerol fermentation produced significantly less acetic acid. Utilizing a fed-batch culture in which both glycerol and yeast extract were fed, 19.0 g/l of succinic acid at a yield of 1.60 g succinic acid/g glycerol consumed was produced by A. succiniproducens with minimal byproduct formation [48] (Table 1). Actinobacillus succinogenes has also been exploited for the conversion of glycerol to succinic acid utilizing anaerobic fermentations with carbon dioxide sparging [49].…”
Section: Succinic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with Anaerobiospirillum succiniproducens, succinic acid production from glycerol or glucose fermentations with a carbon dioxide atmosphere, revealed that glycerol fermentation produced significantly less acetic acid. Utilizing a fed-batch culture in which both glycerol and yeast extract were fed, 19.0 g/l of succinic acid at a yield of 1.60 g succinic acid/g glycerol consumed was produced by A. succiniproducens with minimal byproduct formation [48] (Table 1). Actinobacillus succinogenes has also been exploited for the conversion of glycerol to succinic acid utilizing anaerobic fermentations with carbon dioxide sparging [49].…”
Section: Succinic Acidmentioning
confidence: 99%
“…The oxidative branch results in the conversion of glycerol into the glycolytic intermediate DHAP, a key node for both the reductive branch and ethanol synthesis. In addition, other microorganisms have been shown to possess the ability to ferment glycerol with no reported propanediol-producing capability, including Propionibacterium acidipropionici [53] and Anaerobiospirillum succiniproducens [48]. However, the mechanisms and pathways mediating the dissimilation of glycerol under anaerobic conditions have not been investigated.…”
Section: Box 2 Metabolic Models For the Fermentative Utilization Of mentioning
confidence: 99%
“…The glycerol is an easily available and adequate carbon source for microorganisms (Lee et al, 2001;Tickell, 2003). It can intensify microbial activity which can help to increase the availability of vegetal nutrient.…”
Section: Introductionmentioning
confidence: 99%
“…Besides products that can be derived from glycerol in one or two reactions further products requiring more complex conversions have been investigated, e.g. succinic acid production with Anaerobiospirillum succiniciproducens (Lee et al 2001) or Escherichia coli (Blankschien et al, 2010, citrate production with Yarrowia lipolytica , ethanol production with Escherichia coli, Saccharomyces cerevisiae, or Hansenula polymorpha , Shams Yazdani & Gonzalez, 2008, production of amino acids with Corynebacterium glutamicum (Rittmann et al, 2008), or propionate production with Propionibacteria (Himmi et al, 2000). Crude glycerol preparations from biodiesel factories differ considerably from the pure chemical glycerol, e.g.…”
Section: Introductionmentioning
confidence: 99%